68 Risks and benefits using a mobile-phone positioning system to activate lay volunteers to out-of-hospital cardiac arrests. (16th April 2018) - Andelius, L; Hansen, CM; Lippert, FK; Kjølbye, JS; Karlsson, L; Møller, S; Torp-Pedersen, C; Gislason, GH; Folke, F
Abstract : Aim: The 'HeartRunner'-system is a mobile-phone positioning system that activates lay volunteers (heart-runners) to retrieve a publicly accessible automated external defibrillator (AED) and start resuscitation in out-of-hospital cardiac arrests (OHCAs). We investigated the risks and benefits of the HeartRunner-system. Method: In cases of suspected OHCA, the Emergency Medical Dispatch Centre activates the HeartRunner-system which automatically alerts heart-runners<1, 100 m from the OHCA. After the alarm, all activated heart-runners receive an electronic survey regarding system functionality and physical and psychological impact of the experience. Data was collected from September 1 st to December 31th 2017. Results: In 273 cases, 1215 heart-runners were activated and received the survey. The response rate was 94.5%. Of 672 accepting the alarm, 69.6% (n=468) arrived at the OHCA. Of those, 32.3% (n=151) arrived prior to the ambulance, which was in 36.3% (99/273) of all cases. In 14.3% (n=39/273) of the cases, a heart-runner applied an AED, and in 28.2% (n=11/39) defibrillated the patient. Only 0.4% (n=3) reported minor physical injuries, and 0.7% (n=5) reported severe psychological distress. They were subsequently debriefed by health care professionals and screened for post-traumatic stress symptoms; one person showed signs of moderate distress. Conclusion: Using a mobile-phone positioning system, heart-runners were able to arrive prior to the ambulance in one third of all cases. Of those, every fourth applied an AED of which 28.2% defibrillated the patient. It seems physically and psychologically safe for heart-runners to attend in OHCA resuscitation. Conflict of interest: None Funding: Dr. L. Andelius is supported by a fund from The Danish foundation TrygFonden, who has no influence on study design; in the collection, analysis, or interpretation of data.